Step
*
2
2
1
1
of Lemma
rem_antisym
.....wf..... 
1. ∀a:ℤ. ∀b:ℕ+.  ((-a rem b) = (-(a rem b)) ∈ ℤ)
2. a : ℤ
3. b : ℤ-o
4. ¬(0 ≤ b)
⊢ -b ∈ ℕ+
BY
{ TACTIC:(MemTypeCD THEN Auto) }
1
.....set predicate..... 
1. ∀a:ℤ. ∀b:ℕ+.  ((-a rem b) = (-(a rem b)) ∈ ℤ)
2. a : ℤ
3. b : ℤ-o
4. ¬(0 ≤ b)
⊢ 0 < -b
Latex:
Latex:
.....wf..... 
1.  \mforall{}a:\mBbbZ{}.  \mforall{}b:\mBbbN{}\msupplus{}.    ((-a  rem  b)  =  (-(a  rem  b)))
2.  a  :  \mBbbZ{}
3.  b  :  \mBbbZ{}\msupminus{}\msupzero{}
4.  \mneg{}(0  \mleq{}  b)
\mvdash{}  -b  \mmember{}  \mBbbN{}\msupplus{}
By
Latex:
TACTIC:(MemTypeCD  THEN  Auto)
Home
Index